A modular one-switch three-phase Single Ended Primary Inductor (SEPIC) rectifier - Bashar, Khandaker Lubaba; Islam, Samia M.Naeemul; Choudhury, Mohammad Ali A.Shoukat; Abedin, Amina Hasan; Uddin, Mohammad Nasir (© 2017 IEEE, 2018)
This conference paper was published in the IEEE International Conference on Industrial Technology, ICIT 2017; Hilton TorontoToronto; Canada; 23 March 2017 through 25 March 2017 [© 2017 IEEE] and the definite version is available at : http://doi.org/10.1109/ICIT.2017.7913053 The Journal's website is at: https://ieeexplore.ieee.org/document/7913053/